Effect of Marine Diesel and Biodiesel Blend on basic Fuel Properties: A Novel Study for Marine Diesel Engines - Idubor Fabian. I; Agberegha OrobomeL. (International Journal of Engineering and Management Research, 2019)
Biodiesel has received increased attention due to higher cetane number, flash point, lesser exhaust emission compared to diesel fuel. Important correlation of density, viscosity and flash point with diesel fuel for spectrum blends are still lacking. Therefore, in this study, waste oil biodiesel (WOB) was procured and blended with diesel fuel (B0) at volume ratios of 25%, 50% and 75%, which are referred to as B25, B50 and B75. The important fuel properties of the biodiesel-diesel fuel blends were also analyzed and correlations were established for the WOB and B0 blends. The result obtained show that density and viscosity with flash point can be modelled with the fourth degree and second degrees equations respectively and can be useful for industrial applications of diesel and biodiesel blends.